Association of Fasting Serum Lipid Level with Diabetic Retinopathy - Raihan, Mohammad Hussain; Rashid, Md Shoeb Ur; Morshed, Sumon Shahrior; Dipa, Mossammat; Akter, Nasima; Shuchi, Tarzeen Khadiza (Journal of National Institute of Ophthalmology, 2023)
Background: Diabetic eye disease is now one of the major causes of blindness in the world. Elevated serum lipids have been speculated to cause or exacerbate diabetic retinopathy by several mechanisms. Objectives: To observe the relationship of serum lipids with diabetic retinopathy. Methods: This cross sectional observational study was carried out in the Department of Ophthalmology, Combined Military Hospital Dhaka, from July 2016 to December 2016. A total of 150 patients were selected for the study and divided into three groups. Group I comprises 50 patients with different stages of retinopathy. Group II comprises 50 diabetic patients without retinopathy, and group III comprises 50 non diabetic healthy control people. Results: The age range was 27 to 70 years; Male and female ratio was 1.54:1. The mean duration of diabetes in group I was 9.82 ± 4.04 years and 8.38 ± 3.39 years in group II. Measuring Fasting lipid profile in between group I and group II and between group I and III were statistically significant (p< 0.001). Conclusion: Patients with diabetic retinopathy have been found to have a close association with elevated serum lipid levels. J.Natl.Inst.Ophthalmol.2023;6(1): 16-20